Feasibility Of Electronic Comics For The Introduction Of Clean And Healthy Living Behaviors At Mulya Fajar Kindergarten, Indragiri Hulu Regency - Rivo Panji Yudha; Rika Sepriani (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research aims to develop an electronic comic (e-comic) as an innovative learning medium for introducing clean and healthy living behaviors at Mulya Fajar Kindergarten in Indragiri Hulu Regency. The e-comic is designed to enhance the interest and understanding of 4-5-year-old children in the importance of maintaining a clean and healthy lifestyle, which is a crucial aspect of early childhood education. The research began with an initial study to gather information and understand the current situation of teaching and learning activities at Mulya Fajar Kindergarten, particularly in the context of teaching about clean and healthy living. The researcher conducted observations and interviews with the school supervisor and teachers to identify any issues in the learning process, especially related to the introduction of clean and healthy living behaviors. The design of the e-comic was planned in stages, considering the appropriate materials for children to learn about clean and healthy living, the amount of information to be introduced, and any obstacles faced by teachers or students in teaching these concepts. The e-comic was created using the Canva platform, which offers a variety of tools for drawing illustrations, applying color palettes, adding text and dialog balloons, and incorporating graphic elements relevant to the theme of cleanliness and health. The final product of this research is an e-comic that has been tested and revised to ensure its quality and effectiveness. The e-comic is intended for use as an electronic learning medium for children aged 4-5 at Mulya Fajar Kindergarten in Indragiri Hulu Regency. The research also includes a statement of originality, confirming that the work is the researcher's own and free from plagiarism, and a validation sheet for the progress of the research project. The e-comic is expected to be a specific product that can be used to introduce clean and healthy living behaviors to young children, promoting interactive visual narratives that can develop children's language skills and creativity, as well as providing teachers with creative and innovative experiences to teach these concepts.